A Meta-Analytic Approach to Determine the Effectiveness of Exercise Interventions on Abdominal Fat and Liver Enzymes in Overweight and Obese Youth. - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible